The impact of performance analysis on the financial management and control at public universities in Bosnia and Herzegovina Federation - Čergić, Fuad (Array, 2019)
Organizations in today's extremely competitive environment need to devote significant time, energy as well as human and financial resources to the measurement of their efficiency, in order to increase their profit, reduce costs, better plan their assets and manage their budgets, as well as to improve budget controls and risk assessment. Therefore, they need performance models, including the Balanced Scorecard. Primarily intended for profit organizations, the Balanced Scorecard is today used in the public sector, as well. This paper presents the research into the utilization of the Balanced Scorecard in the public sector, examining whether the performance of higher education institutions may be improved by the design and utilization of the Balanced Scorecard model.